O fetiche da mercadoria “verde” : a questão ambiental na construção social da imagem do etanol brasileiro - Gameiro, Mariana Bombo Perozzi (2017)
This research aims to understand the social construction of the image of Brazilian ethanol, with special attention to the period from 2003 to 2014, through the investigation of the discourses that contribute to the formation of regimes of truth about the "green commodity" and the articulations between political and economic actors interested in it. The period is marked by the (re)birth of ethanol in the national market under the appeal of a "sustainable product", apparently desired by society, who would demand renewable energy sources that can replace polluting and depleting fossil fuels. In contrast to these discourses we can find those who point out that sugarcane ethanol carries within itself social relations historically marked by bad working conditions, by the concentration of land and power, by the depreciation of natural resources and by the competition with food production. In this context, many efforts have been undertaken by governments and the sugar and ethanol industry to overcome the contradictions in which ethanol is involved, in order to make it an internationally accepted commodity. The thesis considers, therefore, that the process of production of the green commodity involves works that go beyond those necessary for the materialized constitution of the product, also requiring a work of symbolic production, not always perceived like that, of which science is a fundamental part. The thesis then proposes that the green commodity is composed by particular types of value (“collective use value” and a “ethical exchange value”). These values, which are found in addition to traditional values described by sociological theories, mark the specificities of a type of commodity that objectively and symbolically results of capitalistic processes boosted by moral justifications. By understanding the market as a result of political, cultural, and axiological disputes that surpass the economic sphere, and searching the representations about Brazilian ethanol, this thesis analytically dialogues with rural sociology and environmental sociology, maintaining a strong interface with the field of economic sociology. Methodologically, qualitative procedures of social research were employed, with emphasis on semi-structured interview techniques, biographies and document analysis.